(untitled) (Geography and Tourism, 2021)
The article aims to outline the problem of transporting illegal plant and animal souvenirs by tourists and to analyse the issue from the perspective of Poland. Tourists’ interest in buying wildlife souvenirs is varied, ranging from live animals and plants to food products, leather and wooden goods, and medicines. Travellers buying illegal souvenirs of plant and animal origin often unwittingly contribute to the extinction of the most endangered plant and animal species. The number of CITES specimens seized in Poland annually is approximately 134 between 2009 and 2018 on average. In 2018 alone, nearly 14 thousand specimens were confiscated. These confiscations were largely directed towards Ukraine. However, despite the fact that the problem is acknowledged in the country, and legal regulations have been introduced to counteract it, the tourism sector seems to be oblivious to the problem, and the subject does not appear in the scope of activities pursued by organizations related to the development and promotion of tourism. So far it has rarely been mentioned in the scientific literature, including the field of tourism. The authors hope that the presented analyses will draw attention to the problem and lead to the implementation of more sustainable practices In Polish tourism.